WorkWays: interacting with scientific workflows. (21st May 2015) - Nguyen, Hoang Anh; Abramson, David; Kipouros, Timoleon; Janke, Andrew; Galloway, Graham
Summary: WorkWays is a science gateway that supports human‐in‐the‐loop scientific workflows. Human–workflow interactions are enabled by a dynamic Input Output (IO) model, which allows users to insert data into, or export data out of, a continuously running workflow. WorkWays has been used to solve a number of scientific problems where the user wishes to examine intermediate results in order to interact with the computation as the workflow progresses. This interactive capability not only provides better insights into the computation but also allows users to focus on different input parameter combinations. We have implemented a variety of data types and modes of interaction to account for a wide range of use cases and application domains. This paper demonstrates the applicability of WorkWays on three use cases from different domains. Copyright © 2015 John Wiley & Sons, Ltd.